2020
DOI: 10.1002/ejsp.2651
|View full text |Cite
|
Sign up to set email alerts
|

Altruistic or selfish? Responses when safety is threatened depend on childhood socioeconomic status

Abstract: Altruism is an effective method of coping with threats. This research explored the relationship between childhood socioeconomic status (SES) and altruism under different situations. The results of five studies provided reliable evidence that safety‐threat conditions moderated the relationship between childhood SES and altruism. Individuals with higher childhood SES exhibited higher altruistic intentions (Studies 1 and 2) and behaviors (Study 3) when they were manipulated to imagine a safety threat scenario (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…If the desire for control is a key mechanism underlying consumers' pattern-seeking, an individual difference in perceived control over the environment should influence our prediction. As described earlier, individuals' early-life environments shape various aspects of behavior in adulthood (Griskevicius et al, 2011;Hill et al, 2016;H. Li et al, 2020;Wang et al, 2020;Whelan & Hingston, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 88%
See 1 more Smart Citation
“…If the desire for control is a key mechanism underlying consumers' pattern-seeking, an individual difference in perceived control over the environment should influence our prediction. As described earlier, individuals' early-life environments shape various aspects of behavior in adulthood (Griskevicius et al, 2011;Hill et al, 2016;H. Li et al, 2020;Wang et al, 2020;Whelan & Hingston, 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 88%
“…According to an evolutionary perspective, early-life experiences can internalize the manners in which people respond to environments (Ellis et al, 2009). A growing body of research has shown that environmental conditions encountered during early childhood influence many aspects of individuals' lives such as cognitive performance (Nisbett, 2009), altruistic behavior (H. Li et al, 2020), eating behavior (Hill et al, 2016), impulsivity, (Griskevicius et al, 2011), risk-taking, and mental discounting . Early-life experiences are commonly reflected in childhood SES-people growing up in lower SES environments encounter more unpredictable early-life experiences than those who grew up in higher SES environments (Mittal & Griskevicius, 2014).…”
Section: Childhood Sesmentioning
confidence: 99%
“…First, our paper extends the literature on authenticity by linking external threats like COVID‐19 and consumers' attitudes toward products promoted with authenticity appeals. Research has shown that authenticity positively influences consumers' perceptions and values (e.g., Lee et al, 2019 ; Li et al, 2019 ; Liang et al, 2018 ) and leads to positive advertising outcomes (e.g., Chalmers & Price, 2009 ; Zhang et al, 2014 ). For example, Hamby et al ( 2019 ) showed that sharing a story about the founders' original purpose of the business could increase the perceived authenticity of the brand.…”
Section: Discussionmentioning
confidence: 99%
“…Research has documented that authenticity reflects a product's quality and trust level (van den Bosch et al, 2005 ), enhances message receptivity (Labrecque et al, 2011 ), and increases perceived quality (Moulard et al, 2014 ) and purchase intentions (Napoli et al, 2014 ). Accumulated evidence also suggests that authenticity generates positive consumer responses (e.g., del Barrio‐García & Prados‐Peña, 2019 ; Lee et al, 2019 ; Li et al, 2019 ). For example, Lee et al ( 2019 ) found that authentic Korean cosmetics enhanced consumer perceptions of quality and led to higher purchase intention.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Individuals with adequate family resources during childhood have stable interpersonal bonds, enjoy cooperation, and are more likely to trust and act altruistically (Stamos et al, 2019 ). Li et al ( 2019 ) found that students with a higher childhood socioeconomic status (SES) exhibited higher altruistic intentions and behaviors when facing or imagining a threat scenario in three experimental environments. Having lower financial conditions in childhood was associated with lower mental health and well-being in adulthood.…”
Section: Introductionmentioning
confidence: 99%